2006
DOI: 10.1007/s10295-006-0097-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vitreoscilla hemoglobin in Gordonia amarae enhances biosurfactant production

Abstract: The gene (vgb) encoding Vitreoscilla (bacterial) hemoglobin (VHb) was electroporated into Gordonia amarae, where it was stably maintained, and expressed at about 4 nmol VHb g À1 of cells. The maximum cell mass (OD 600 ) of vgb-bearing G. amarae was greater than that of untransformed G. amarae for a variety of media and aeration conditions (2.8-fold under normal aeration and 3.4-fold under limited aeration in rich medium, and 3.5-fold under normal aeration and 3.2-fold under limited aeration in mineral salts me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…Only one study detailing the use of recombinant strains for trehalose lipid production has been reported. A recombinant Gordonia amarae was developed by insertion, stable maintenance and expression of the Vitreoscilla hemoglobin gene (vgb), resulting in enhanced production of the trehalose lipid biosurfactants in the engineered strain [42].…”
Section: Optimisation Of Productionmentioning
confidence: 99%
“…Only one study detailing the use of recombinant strains for trehalose lipid production has been reported. A recombinant Gordonia amarae was developed by insertion, stable maintenance and expression of the Vitreoscilla hemoglobin gene (vgb), resulting in enhanced production of the trehalose lipid biosurfactants in the engineered strain [42].…”
Section: Optimisation Of Productionmentioning
confidence: 99%
“…Other microbial responses to these two classes of stressor include the stabilization of nucleic acid structures, gene-regulating processes and membrane structures; there is a strong resemblance between the cellular responses to hydrophobic substances and hydrophilic chaotropes regardless of microbial taxon or specificity of the chemical compound (e.g. Mizushima et al, 1993;Dogan et al, 2006;Radniecki et al, 2008;Trautwein et al, 2008). Compatible solutes may also protect nucleic acid structures and those of proteins involved in nucleic acid synthesis, repair and binding (Xie and Timasheff, 1997); it has been suggested that nucleic acids represent the failure point of microbial cells under other extreme conditions (see Pitt, 1975).…”
Section: Protein Stabilizationmentioning
confidence: 99%
“…In the genus Gordonia, the most extensively studied species for the production of SACs is G. amarae (Iwahori et al 2001;Pagilla et al 2002;Dogan et al 2006). Franzettiet al (2008 reported the production of at least two types of SACs byG.…”
Section: Resultsmentioning
confidence: 99%